Finding purple America the South and the future of American cultural studies - Smith, Jon (The new Southern studies, 2013)
"The new southern studies has had an uneasy relationship with both American studies and the old southern studies. In Finding Purple America, Jon Smith, one of the founders of the new movement, locates the source of that unease in the fundamentally antimodern fantasies of both older fields. The old southern studies tends to view modernity as a threat to a mystic southern essence--a dangerous outside force taking the form of everything from a "bulldozer revolution" to a "national project of forgetting." Since the rise of the New Americanists, American studies has also imagined itself to be in a permanent crisis mode, seeking to affiliate the field and the national essence with youth countercultures that sixties leftists once imagined to be "the future." Such fantasies, Smith argues, have resulted in an old southern studies that cannot understand places like Birmingham or Atlanta (or cities at all) and an American studies that cannot understand red states. Most Americans live in neither a comforting, premodern Mayberry nor an exciting, postmodern Los Angeles but rather in what postcolonialists call "alternative modernities" and "hybrid cultures" whose relationships to past and future, to stability and change, are complex and ambivalent. Looking at how "the South" has played in global metropolitan pop culture since the nineties and at how southern popular and high culture alike have, in fact, repeatedly embraced urban modernity, Smith masterfully weaves together postcolonial theory, cultural studies, Lacanian psychoanalysis, and, surprisingly, marketing theory to open up the inconveniently in-between purple spaces and places that Americanist and southernist fantasies about "who we are"have so long sought to foreclose."--Publisher's website